Apalancamiento financiero y rentabilidad de la empresa La Restinga 2024 - Ramirez Cardenas, Erick Romel (2025)
This research was intended to determine how financial leverage impacts on the profitability of the company La Restinga 2024. The study was basic, quantitative, correlational of non-experimental and transversal design. The sample for the current study was 30 customers. In the results, we can see that, of a total of 30 respondents in financial leverage and profitability of the company La Restinga 2024, 2.0% responded that almost never executes financial leverage of the company La Restinga 2024, therefore, 12.0% comment that never, in addition 18.0% said that sometimes, on the other hand, 28.0% expressed that they almost always expressed that they almost always expressed that they almost always expressed that they almost always expressed that they almost always expressed that 28.0% said that 28.0% expressed that they almost always expressed that 40% I affirm that it always executes financial leverage of the company La Restinga 2024. It was concluded that the financial leverage positively impacts the profitability of the company Restinga 2024. This is due to the fact that the financing by debt has allowed to take advantage of investment opportunities with a financial cost less than the generated yield, which has increased the return on the assets. However, this benefit is conditioned to efficient indebtedness and a stable economic environment that allows us to comply with financial obligations without compromising the liquidity of the company.